Kinetic Studies on The Oxidation of 1-Phenyl Ethanol and Its para-Substituted Derivatives by Potassium Dichromate in Aqueous Acetic Acid Medium - Radhakrishnan Nair, T.D.; Zuhara, M. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of 1-phenyl ethanol by potassium dichromate in aqueous acetic acid medium containing sulphuric acid have been carried out. The rate of reaction was found to be first order with respect of both [substrate] and [oxidant]. The rate was found to increase with increasing percentage of acetic acid and [sulphuric acid]. The rate was found to be increased by the presence of electron donating substituents and retarded by electron withdrawing groups. Various thermodynamic parameters were calculated using Arrhenius and Frying equation using the data obtained from temperature studies. Based on the observations suitable mechanism has been proposed. Radical formation was ruled out using acrylonitrile.